Basal leaf senescence in a sunflower (Helianthus annuus) canopy: responses to increased R/FR ratio - Rousseaux, Maria Cecilia (2000)
Senescence of lower leaves (LS) begins before anthesis in sunflower crop canopies. Using isolated field‐grown sunflower plants, it has previously been shown that pre‐anthesis LS is dependent on photosynthetic photon flux density (PPFD) and is hastened by increases in far‐red light. We tested the hypothesis that increasing the red/far‐red ratio (R/FR) perceived by basal leaves within canopies delays LS. To do this, light impinging on the lower surface of north‐oriented 8th leaves (cotyledons=0) of crops with maximum leaf area indexes of 3.3 (Experiment 1) and 2.4 (Experiment 2) was enriched (+8.33 μmol m−2 s−1) with red light using light emitting diode (LED) panels. LED panels constructed with unlit LED or with green LED (PPFD slightly greater than the red LED panels, to compensate for lower efficiency) were used as controls. Compared with controls, additional R significantly (P<0.05) increased R/FR perceived by the lower surface and significantly (P<0.01) delayed LS. On average, leaf duration, as time between full expansion and a 70% diminution of chlorophyll content, was 5 days greater for leaves receiving extra red light (maximum observed LD=27 days). We conclude that an increase in the R/FR ratio can delay LS in crop canopies.